FACTOR ANALYSIS OF PERSONAL BRANDING FORMING OF PSSI FORMER GENERAL PERSON EDY RAHMAYADI - Fibriyani Nur Aliya (Profetik: Jurnal Komunikasi, 2020)
Abstrak. Personal branding seorang eksekutif merupakan proses menjaga identitas, reputasi, dan citra publik seseorang. Mantan Ketua Umum PSSI, Edy Rahmayadi, menerima petisi online yang memaksanya mundur. Petisi online tersebut dipicu oleh maraknya pemberitaan di media massa dan media sosial. Meme kontroversial yang dibuat oleh Edy menanggapi pertanyaan jurnalis dibuat dan disebarluaskan di internet. Diketahui bahwa pengguna internet didominasi oleh pengguna internet. Berdasarkan hal tersebut, maka penelitian ini bertujuan untuk menganalisis faktor personal branding Edy Rahmayadi dalam pandangan kaum milenial sebagai pengguna internet dan media sosial terbesar. Variabel origin yang digunakan dalam penelitian ini. adalah Authentic Personal Branding variable. Hasil penelitian menunjukkan empat faktor baru terbentuk, yaitu Mampu menjelaskan sebelas faktor asal dan faktor personal branding pembentuk Edy Rahmayadi, Faktor pertama adalah Faktor Keunggulan, faktor kedua adalah Faktor Inovasi, Faktor ketiga adalah Faktor Pakar, dan Faktor keempat adalah Keunikan. Faktor yang menjelaskan variabel asal adalah faktor keunggulan.Abstract. An executive's personal branding is the process of maintaining one's identity, reputation and public image. Former PSSI Chairperson, Edy Rahmayadi, received an online petition that forced him to resign. This is happened when he handled the crisis that occurred in the PSSI organization. The online petition was triggered by the rise of news coverage on him in the mass media and social media. The controversial memes made by Edy in response to journalists' questions were made and disseminated on the internet. It is known that internet users are dominated by millennial generation, where this is directly proportional to social media users. Based on this, this study aims to analyze Edy Rahmayadi's personal branding factors in the view of millennials, as the biggest internet and social media user. The origin variable uses in this study is the Authentic Personal Branding variables. The results shows four new factors formed, which are able to explain eleven origin factors and the personal branding factors forming Edy Rahmayadi. The first factor is the Excellence Factor, the second factor is the Innovation Factor, the third Factor is the Expert Factor, and the fourth Factor is Uniqueness. The most dominant factor explaining the origin variable is the excellence factor.